Evaluasi kualitas layanan aplikasi Pustabiblia menggunakan metode digiQUAL - Suryanto Suryanto; Ervina Desi Anggraeni; Majidah Majidah (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This research focuses on evaluation of digital library quality services using DigiQUAL method. This research provide evaluation results and knowledge regarding the quality of Pustabiblia application services to support further development. Data Collection Methods. This is quantitative research with descriptive analysis. Data was taken from a sample of 80 respondents. Data Analysis. Data analysis techniques used mean and grand mean with Microsoft Excel application to calculate the average service quality variable. The categorization criteria was conducted. Results and Discussion. The results showed that it was in the high or good category with a service quality index of 3.64. The lowest index in the research was the Resource Use with a value of 3.39. Conclusion. In general, the quality of the library application service is already in the “good” category but it can still be improved to be in the “very good” category. Further, there needs to be promotion and recommendations regarding the use of the library application so that students can access the library application more often, particularly to meet student information needs.